Oxidative stress and antioxidant responses to progressive resistance exercise intensity in trained and untrained males - H Çakır-Atabek; F Özdemir; R Çolak (Termedia Publishing House, 2015)
The relationship between oxidative stress and some exercise components of resistance exercise (e.g. intensity, exercise volume) has not been clearly defined. Additionally, the oxidative stress markers may respond differently in various conditions. This study aims to determine the effects of progressive intensity of resistance exercise (RE) on oxidative stress and antioxidants in trained and untrained men, and also to investigate the possible threshold intensity required to evoke oxidative stress. RE trained (N=8) and untrained (N=8) men performed the leg extension RE at progressive intensities standardized for total volume: 1x17 reps at 50% of one-repetition maximum (1RM); 1x14 reps at 60% of 1RM; 1x12 reps at 70% of 1RM; 2x5 reps at 80% of 1RM; and 3x3 reps at 90% of 1RM. Blood samples were drawn before (PRE) and immediately after each intensity, and after 30 minutes, 60 minutes and 24 hours following the RE. Lipid-hydroperoxide (LHP) significantly increased during the test and then decreased during the recovery in both groups (p<0.05); the POST-24 h LHP level was lower than PRE-LHP. Protein carbonyl (PCO) and superoxide dismutase (SOD) significantly increased (p 0.05). The results indicated that there was no significant training status x intensity interaction for examined variables (p>0.05). Standardized volume of RE increased oxidative stress responses. Our study suggests that lower intensity (50%) is enough to increase LHP, whereas higher intensity (more than 80%) is required to evoke protein oxidation.